Creation and the Symbiosis of Science and Judaism - Samuelson, Norbert Max (Zygon, 2002)
It seems to me that the critical questions that science and natural philosophy raise for Jewish theology are the following: Does God evolve? Does the universe have or even need an interpretation, specifically with reference to the fact that most of the universe most of the time is uninhabitable, and there may be many more than one universe? Does the universe need a beginning? What is distinctive about human consciousness, intelligence, and ethics in the light of evidence for evolution from all of the life sciences? Finally, will both life and the universe end? These questions are not only modern. They contain all the primary issues that have dominated rabbinic thought. That agenda can be summarized in six topics: How should we model what we believe about (1) God, (2) the world, and (3) the human being; and how should we understand the relations between them, that is, between (4) God and the world (or, creation), (5) God and the human (or, revelation), and (6) the human and the world (or, redemption)? In this paper I focus on the fourth issue, creation. My answer is presented in detail in my Judaism and the Doctrine of Creation(Samuelson 1994). Here I shall summarize my conclusions there concerning science, Jewish texts, and the correlation between them.